If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = -5y + 2(y + -3) Reorder the terms: 6 = -5y + 2(-3 + y) 6 = -5y + (-3 * 2 + y * 2) 6 = -5y + (-6 + 2y) Reorder the terms: 6 = -6 + -5y + 2y Combine like terms: -5y + 2y = -3y 6 = -6 + -3y Solving 6 = -6 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 6 + 3y = -6 + -3y + 3y Combine like terms: -3y + 3y = 0 6 + 3y = -6 + 0 6 + 3y = -6 Add '-6' to each side of the equation. 6 + -6 + 3y = -6 + -6 Combine like terms: 6 + -6 = 0 0 + 3y = -6 + -6 3y = -6 + -6 Combine like terms: -6 + -6 = -12 3y = -12 Divide each side by '3'. y = -4 Simplifying y = -4
| 5(x-2)+2x+6=38 | | 2sin^2x+3sinx-5=0 | | 6n+5=7n-3 | | -25+9=t | | 3xsquared+6=81 | | 5x+6y=430 | | (6x-3)(3x+5)=3(7x-5) | | 2//x=0.5 | | 2x+28-8x=12+19x-8 | | 4*(x+2)=4*x+2 | | 6/11w=1/2 | | 2.25x+0.5=8.5+0.25x | | x^2+3xy=10-y^2 | | x^2-3xy=10-y^2 | | ln(x+1)+ln(x-1)-(ln(4x^2-4)-ln(4))=e^5x-300 | | 7k+8+2k=-64 | | 3(x+13)=19 | | 2+4(x-6)=2x+1 | | (4.25*10^9)/(5.76*10^4) | | (4.25x10^9)/(5.76x10^4) | | 88+3x=54*2x | | 4x-2=12-66 | | 6a^2-2ax=0 | | 6x^2-2ax=0 | | 40+0.25m=80 | | 0=-3x^2-6x+4 | | lx^2-kx+8=0 | | x^2-kx-24=0 | | -2n+4=12 | | x^2-4kx+(5k-6)=0 | | 7y^2(y-2)=0 | | f(x)=8/3x^4 |